When migrants do not speak the host country’s language but need mental health care: A protocol for developing a communication intervention - Houda Al Kalaf; Christopher Jenks; Mike Mösko; Ted Sanders; Barbara Schouten (PLoS ONE, 2025)
Migrant clients frequently encounter communication barriers in mental healthcare, primarily driven by language differences that complicate the expression and understanding of psychological distress. Language barriers also affect mental healthcare providers (MHCPs), who often report low confidence and limited skills in navigating cross-linguistic encounters. Inadequate access to trained interpreters, uncertainty about their roles, and a lack of structured training leave MHCPs underprepared to ensure accurate communication and offer person-centred care. Strong collaboration between MHCPs, clients, and interpreters can significantly reduce communication barriers, fostering shared understanding and trust. However, existing initiatives to address language-related challenges in mental healthcare for migrants remain fragmented, lack cultural sensitivity, and are rarely designed or evaluated systematically. This study addresses this need by designing, developing, implementing, and evaluating a structured communication intervention that aims to strengthen MHCPs’ ability to provide care for migrant clients who face language barriers. The intervention mapping (IM) framework is used to conduct an extensive needs assessment, including interviews with MHCPs, clients, and interpreters across multiple countries, to identify communication challenges and inform intervention design. The training program was co-developed with stakeholders and pilot-tested to assess clarity, engagement, and practical relevance. The resulting evidence-informed program seeks to improve therapeutic communication and ultimately support better mental health outcomes for linguistically diverse migrant populations. Protocol Registration This study protocol has been preregistered with the Open Science Framework (OSF) to enhance transparency, reproducibility, and methodological rigour. The registration includes a detailed description of the study objectives, design, intervention components, target population, outcome measures, and planned analyses. Any future amendments to the protocol will be documented and timestamped on the OSF platform to maintain a clear audit trail of changes. The registration is publicly accessible via OSF https://osf.io/g2jk7 .